Selectivity of insecticides used in corn crops to adult Trichogramma atopovirilia (Hymenoptera: Trichogrammatidae) - BRAGA-MAIA, JADER; ANDRADE-CARVALHO, GERALDO; SANTOS-LEITE, MARIA ISABELLA; LOPES DE OLIVEIRA, RODRIGO; MAKYAMA, LETÍCIA (Revista Colombiana de Entomología, 2010)
The aim of this work was to evaluate the toxicity of the insecticides imidacloprid/ß-cyfluthrin (Connect 100/12.5 SC), chlorfenapyr (Pirate 240 SC), chlorpyrifos (Astro 450 EW), novaluron (Rimon 100 CE), spinosad (Tracer 480 SC) and triflumuron (Certero 480 SC), as used in corn crops (Zea mays), to parent generation females and to F1 and F2 generation specimens of Trichogramma atopovirilia. Eggs of Anagasta kuehniella were glued to cardstock strips and placed under a germicidal lamp to kill embryos. These were then sprayed with the chemical products using a Potter tower and exposed to parasitism 24, 48, and 96 hours after application of the compounds for a span of 24 hours. We evaluated the number of dead specimens and the number of eggs parasitized by parent generation females, as well as the percent emergence and parasitic capacity of the F1 and F2 generations. Chlorfenapyr, spinosad, chlorpyrifos, and imidacloprid/ß-cyfluthrin were moderately harmful to adult T. atopovirilia, while novaluron was slightly harmful. Triflumuron was harmless and could be used in integrated pest management programs intended to preserve adult T. atopovirilia in corn crops.